162 OSWESTRY DISABILITY INDEX VERSUS NECK DISABILITY INDEX SCORES IN LUMBAR AND CERVICAL PAIN PATIENTS. Issue 1 (1st January 2007) - Cross, C. C.; Ozoa, G.; Fish, D. E.; Pham, Q.
Abstract : Purpose: The purpose of the study is to determine if the Oswestry Disability Index (ODI) and the Neck Disability Index (NDI) have enough overlap that they can both predict the same functional status in patients with either lumbar or cervical pain. Methods: Patients undergoing evaluation and treatment for pain completed a self-reported survey, which included the ODI, NDI, and Hospital Anxiety and Depression Scale (HADS). Fifty back pain patients and 51 neck pain patients completed the survey. They were further subdivided into groups having either no (0-7) versus possible (8-10) versus probable (11-21) anxiety or depression, based on their HADS scores. Setting: UCLA Spine Center, outpatient. Statistics: SPSS independent t -test and paired t -test Results: Mean ODI score in lumbar patients was 33.1 (SD = 18.7), and the mean NDI score was 29.8 (SD = 19.9). There was a significant effect for the type of survey, t (49) = 3.20, p < .01. Mean ODI score in cervical patients was 28.3 (SD = 16.5), and the mean NDI score was 36.4 (SD = 14.8). There was a significant effect for the type of survey, t (50) = −4.90, p < .001. For patients with an anxiety or depression HADS score of ≤ 10: no difference in the ODI score for back and neck pain, t (79) = −1.60, p > .05; t (88) = −0.72, p > .05; significance for the NDI, t (79) = 2.38, p < .05; t (88) = 3.49, p < .01. Summary: Patients with only lumbar pain showed a significant difference in the values recorded for the ODI when compared with the NDI. The same phenomenon was demonstrated in patients with cervical pain. The mean ODI for all patients did not show a significant difference in the mean between back patients or neck patients. However, the mean NDI score reflected a significant difference in the mean between lumbar and cervical pain patients. Patients with low HADS scores showed a statistically significant difference in the mean between back patients and neck patients completing the NDI. Conclusions: Patients must be assessed with the ODI for back pain and the NDI for neck pain. Although the NDI was based on the ODI, it is a better assessment of functional outcome in neck than back patients. When patients have low anxiety or depression states, the NDI is even better at predicting the functional outcome of neck versus back patients than the ODI.